2014
DOI: 10.1002/pat.3361
|View full text |Cite
|
Sign up to set email alerts
|

Anionic and cationic nanocomposite hydrogels reinforced with cellulose and chitin nanowhiskers: effect of electrolyte concentration on mechanical properties and swelling behaviors

Abstract: Various nanocomposite gels were prepared using cellulose nanowhiskers (CNWs) or chitin nanowhiskers (ChNWs) as reinforcing fillers and hydroxypropyl cellulose (HPC), carboxymethyl cellulose (CMC), or chitosan as network polymers. The use of CNWs with low surface charge induced significant CNWs aggregations, which were well explained by depletion effect. Young's modulus E and swelling ratio Q of CNWs/HPC · CMC gels were highest at zero electrolyte concentration and decreased above 0.01 M electrolyte, whereas st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…Many researchers have focused on creating “all-cellulose” gels with widely available and biocompatible cellulose derivatives. Notably, McKee et al utilized thermoresponsive methylcellulose networks, which formed hydrogels at elevated temperature and were successfully reinforced by CNCs with the storage modulus increasing by nearly an order of magnitude upon addition of 3.5 wt % CNC . The ability of CNCs to effectively reinforce all natural or all-cellulose polymer networks drastically broadens the potential for CNCs in advanced sustainable/green chemistry applications.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Many researchers have focused on creating “all-cellulose” gels with widely available and biocompatible cellulose derivatives. Notably, McKee et al utilized thermoresponsive methylcellulose networks, which formed hydrogels at elevated temperature and were successfully reinforced by CNCs with the storage modulus increasing by nearly an order of magnitude upon addition of 3.5 wt % CNC . The ability of CNCs to effectively reinforce all natural or all-cellulose polymer networks drastically broadens the potential for CNCs in advanced sustainable/green chemistry applications.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Much attention has been focused recently on the utilization of these nanowhiskers as nano-sized fillers in composites, due to their excellent mechanical properties, as well as non-toxicity, biodegradability and ease of large-scale preparation. For example, in the last two decades there have been numerous reports on various types of nanowhisker composites, including films containing matrices of latex or synthetic polymers and fillers of nanowhiskers [19,20,21], high-modulus poly(vinyl alcohol) wet-spun fibers containing uniaxially oriented nanowhiskers [22,23,24,25], hydrogels reinforced by nanowhiskers [26,27] and electrospun fiber mats incorporating nanowhiskers [28].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of CNCs increased the compression modulus of the pure hydro-gel when compared with hydrogels reinforced with Cloisite Na + nanoclay. Araki et al 99 found similar results using CNCs as a reinforcing agent for CMC/HEC hydrogels. McKee et al 100 reported the formation of a hydrogel after dissolution of MC at 60°C in the presence of CNCs with a storage modulus of 900 Pa.…”
Section: Cellulose and Cellulose Derivativesmentioning
confidence: 70%